How Does Technology-Assisted Language Learning (TALL) Influence Elementary School Students Learning? - Jakob, Juvrianto Chrissunday; Hindri Febri Ana Sari; Mouren Wuarlela; Persulessy, Sylvia Irene; Sammy Saptenno; Hizkia Nussy; Ralph Javier; Salawaney, Valy Silas (Institut Agama Islam Negeri Palopo, 2024)
The new era confronts teachers with new tasks and obligations. The use of advanced technology has greatly improved the tradition of teaching English. Technology offers several options, such as making teaching more exciting and efficient. Technology is one of the most powerful drivers of social and linguistic change. As a result, it is necessary to use a learning medium that encourages students to be more enthusiastic about studying. This study intends to apply learning media with technology-assisted to students of SD Negeri Rutong, while also describing assessment media from professionals and users. The development approach utilized is Design and Development with the ADDIE research model (Analyze, Design, Development, Implementation and Evaluation). The results obtained in this research are 1) Interactive multimedia named